Water-soluble sulfonate porphyrin functionalized hyaluronic acid with comb-like structure: Potential photosensitizers for photodynamic therapy. (May 2019) - Cui, Xu; Li, Yanhui; Li, Yanwei; Qiu, Baoguo; Duan, Qian
Abstract: A water-soluble comb-like porphyrin polymer based on hyaluronic acid (HA ) as the main chain and sulfonate substituted tetraphenylporphyrin (TASP ) as side groups, named as HA- g -NH-TPP-(SO3 Na) [(HA- g -TASP )], was designed and synthesized, which could be used as a potential photosensitizer in photodynamic therapy (PDT). This photosensitizer displayed high-water solubility, low dark cytotoxicity, high photocytoxiticy and high singlet oxygen yield ( Φ Δ = 0.86). TheHA- g -TASP was carefully characterized by UV–Vis, FTIR, and 1 H NMR. UV–Vis spectra showed the Q bands of theHA- g -TASP spectrum had a significant red shift about 50 nm to near-infrared (NIR) region compared withTASP, theHA- g -TASP had a smaller energy band gap. The NIR region is known as the transparent window of the organisms, NIR irradiation shows larger penetration distance in tissue. As a novel photosensitizer, HA- g -TASP exhibited low cytotoxicity in dark and also low photocytotoxicity towards normal cells, but performed enhanced photodynamic activity against cancer cells (HeLa cells). As a result, HA- g -TASP with comb-like structure may be a useful photosensitizer for practical photodynamic therapy in the future. Graphical abstract: A water-soluble comb-like porphyrin polymer based on hyaluronic acid (HA ) as the main chain and sulfonato substituted tetraphenylporphyrin (TASP ) as side groups, named asHA- g -TASP, was designed and synthesized, which could be widely used as a potential photosensitizer in photodynamic therapy (PDT).HA- g -TASP is the polymer with comb-like structure which can avoid π-π stacting betweenTASP units, and the photosensitizer displayed high-water solubility, low dark cytotoxicity, high photocytoxiticy and high singlet oxygen yield.Image 1 Highlights: A water-soluble comb-like porphyrin polymer based on hyaluronic acid as the main chain was synthesized, named asHA- g -TASP. In contrast with most photosensitizers, HA- g -TASP had high singlet oxygen yield (Φ Δ = 0.86). TheHA- g -TASP had a smaller energy band gap, lower photodamage effect. TheHA- g -TASP exhibited high-water solubility, good biocompatibility, low dark cytotoxicity, high photocytoxiticy.